The integrative model of emotional intelligence - Andreyeva, Iryna N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article presents the author’s integrative structural model of emotional intelligence, which has a three-level structure («individual’s intellect», «intelligence of the subject of activity» and «personality intelligence»). The first level is characterized by the parameters of temperament (ergichnost, tempo, plasticity, emotionality); the second – the parameters of the instrumental (experimental, strategic) and individual-personal (interpersonal and intrapersonal) emotional intelligence; the third – personal factors (general intelligence, sociability, social courage, emotional stability, adaptability, acceptance of oneself and others, emotional comfort, emotional creativity). The results of empirical verification of the model are presented.
Keywords: emotional intelligence; type, species and subtype of emotional intelligence; experienced and strategic emotional intelligence; interpersonal and intrapersonal emotional intelligence; emotional competence